Critical Roles of the Circadian Transcription Factor BMAL1 in Reproductive Endocrinology and Fertility - Jiang, Yin; Li, Shiping; Xu, Wenming; Ying, Junjie; Qu, Yi; Jiang, Xiaohui; Zhang, Ayuan; Yue, Yan; Zhou, Ruixi; Ruan, Tiechao; Li, Jinhui; Mu, Dezhi (Frontiers in Endocrinology, 2022)
Brain and muscle aryl-hydrocarbon receptor nuclear translocator like protein1 (BMAL1), a core component of circadian oscillation, is involved in many physiological activities. Increasing evidence has demonstrated the essential role of BMAL1 in reproductive physiology. For instance, BMAL1-knockout (KO) mice were infertile, with impaired reproductive organs and gametes. Additionally, in BMAL1-KO mice, hormone secretion and signaling of hypothalamus-pituitary-gonadal (H-P-G) hormones were also disrupted, indicating that H-P-G axis was impaired in BMAL1-KO mice. Moreover, both BMAL1-KO mice and BMAL1-knockdown by small interfering RNA (siRNA) in vitro cultured steroidogenic cells showed that BMAL1 was associated with gonadal steroidogenesis and expression of related genes. Importantly, BMAL1 also participates in pathogenesis of human reproductive diseases. In this review, we elaborate on the impaired reproduction of BMAL1-KO mice including the reproductive organs, reproductive endocrine hormones, and reproductive processes, highlighting the vital role of BMAL1 in fertility and reproductive endocrinology.